Criminal and Legal Characteristics of Criminal Intent - VERESHA, Roman V. (Journal of Advanced Research in Law and Economics, 2017)
This paper considers the problems of the criminal and legal characteristics of criminal intent. The author analyzed the peculiar features of criminal intent as an element of mens rea . The conducted analysis allows stating that the criminal law of certain countries displays a tendency of mostly recognizing criminal intent not as an obligatory element of crimes. The paper substantiates the need for recognizing criminal intent as one of the elements of mens rea , which will allow determining the real intent of the crime and administering the appropriate type and amount of penalty. The study determined that criminal intent is a psychological phenomenon. Therefore, the issues of its analysis and study should be solved at levels, related to psychology and criminology, which will affect the research results, obtained within the framework of one scientific branch, and the setting of research questions and elaboration of conceptual elements regarding this subject in other scientific branches. The paper defines criminal intent, which should be viewed as substantial and outlined features of a conscious imaginary image of the future desired result, which determines the orientation and ordering of various types of criminal activity. Based on a scientific approach to the theoretical determination of intent in criminal law and its place in the mens rea of corpus delicti , the author suggests relating criminal intent to the optional elements of mens rea .